An evaluation of budget allocation and expenditure patterns of Sedibeng district municipality on service delivery - Imuezerua, Emmanuel Oiseomaye (Vaal University of Technology, 2012)
The delivery of service to communities by the municipalities has become a major challenge due to the backlog of service delivery created by the apartheid government in South Africa. The recognition however of local government as a tier of government has gained a new dynamic role as instrument of service delivery. The ultimate objective of this study is to determine the nature of budgetary procedure applicable to the municipality and also examine the budgetary allocation of Sedibeng District Municipality with regard to service delivery. The empirical study consisted of a structured questionnaire handed out to a sample population of officials at Sedibeng District Municipality. The officials were asked to respond to questions on budget allocation and compilation and how service is delivered. A total of thirty - four questionnaires were returned from the forty issued, which generated an 85% response rate. A semi structured interview was also conducted with staff of the budget unit and the Integrated Development Plan unit. The validity and reliability of the data was measured using the Cronbach’s Alpha (a statistical test used in order to generate internal consistency of the questionnaire) and analysed by regression analysis. However the findings of the empirical investigation indicated that although the municipality claim to operate the incremental method of budgeting, the zero based method and trend analysis based method are used in certain sections of the budget which contributes to shortfall in service delivered to the communities. The study concluded with a number of recommendations. These address the short comings and improvements that can be made for effective service delivery to communities.
M. Tech. (Department of Cost and Management Accounting, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Budgetary allocation; Expenditure patterns; Service delivery; Municipality; Dissertations, Academic -- South Africa.; Municipal services -- South Africa -- Sedibeng District Municipality.; Local government -- South Africa -- Sedibeng District Municipality.; Municipal finance -- South Africa.